PARTISIPASI MASYARAKAT TERHADAP KEGIATAN REHABILITASI MANGROVE DI KECAMATAN CANTIGI, KABUPATEN INDRAMAYU - Qonita Surayya; Cecep Kusmana; Leti Sundawati (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2020)
Mangrove is a unique ecosystem in coastal areas that plays an important role in protecting environment and  can improve human welfare. Mangrove rehabilitation is carried out to restore the declining mangrove ecosystem  and active community involvements are needed to ensure the success of rehabilitation. This study aims to analyze  community participation and formulate strategies to increase community participation in mangrove rehabilitation  activities, which were carried out in three villages in Cantigi Sub-District, Indramayu District, namely Cemara, Cangkring, and Lamaran Tarung. Data on community participation was collected through structured interviews  and analyzed using a Likert Scale. The analytic hierarchy process (AHP) method through in-depth interviews  with eight key informants was conducted to formulate strategy on increasing community participation. The result shows that the level of community participation in mangrove rehabilitation activities in all the study locations is very low. The community is only participates in the activities of collecting mangrove seeds, making planting media, and implementing mangrove planting. The typology of participation is at the manipulative stage, which means  that community participation is only carried out by community representatives, such as members of the mangrove forests farmer group in each village. We recommend that by increasing the intensity of rehabilitation activities as well as providing financial support for mangrove rehabilitation facilities and its infrastructures can improve  community participation